Preparation method of foam copper-based catalytic material for electrochemical degradation of chloramphenicol wastewater

By loading a coordination polymer formed by poly (3-thiopheneamide) and polyaminostyrene on a foam copper matrix, the problem of insufficient performance of existing electrochemical catalytic materials was solved, and efficient and stable chloramphenicol wastewater degradation was achieved, which is suitable for industrial applications.

CN119857534BActive Publication Date: 2025-10-03NORTH CHINA UNIVERSITY OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510065127.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-10-03
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

The existing catalytic materials for electrochemical reduction degradation of chloramphenicol wastewater have poor reduction degradation performance and unsatisfactory repeated stability, making it difficult to meet the requirements of large-scale industrial treatment.

Method used

By loading poly (3-thiopheneamide) and poly (aminostyrene) on the surface of the foam copper matrix to form a poly (3-thiopheneamide)/poly (aminostyrene) copper coordination polymer, the unique conductive properties and the unsaturated d orbital of the copper ion are utilized to promote the formation of active hydrogen and achieve the dechlorination reduction degradation of chloramphenicol.

Benefits of technology

The prepared foam copper-based catalytic material has efficient reduction degradation performance and excellent cyclic reuse stability, and is suitable for large-scale industrial electrochemical reduction degradation of chloramphenicol wastewater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119857534B_ABST
    Figure CN119857534B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a foam copper-based catalytic material for electrochemically degrading chloramphenicol wastewater, comprising the following steps: step [1] loading poly (3-thiopheneamide) on the surface of a foam copper substrate; step [2] synthesizing polyaminostyrene; and step [3] converting the poly (3-thiopheneamide) on the surface of the foam copper substrate into a poly (3-thiopheneamide) / polyaminostyrene copper coordination polymer. The foam copper-based catalytic material prepared by the method of the present invention has high-efficiency and excellent reduction degradation performance and excellent cyclic reuse stability, and is suitable for large-scale industrial electrochemical reduction degradation of chloramphenicol wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chloramphenicol-containing wastewater treatment, in particular to a method for preparing a foam copper-based catalytic material for electrochemically degrading chloramphenicol wastewater. Background Art

[0002] Chloramphenicol is an amide antibiotic and a broad-spectrum bacteriostatic antimicrobial agent. Chloramphenicol binds to the 50S subunit of bacterial ribosomes, reducing the activity of peptidyl transferase and inhibiting bacterial synthesis, thereby achieving its antimicrobial effect. Chloramphenicol has inhibitory effects on Gram-negative and Gram-positive bacteria, including Streptococcus pneumoniae, Haemophilus influenzae, and meningococci. At high concentrations, chloramphenicol has a strong killing effect against Gram-negative bacteria and other bacteria. Due to its widespread use in human healthcare, livestock breeding, bacterial control, and disease treatment, chloramphenicol is entering the soil and aquatic environments in increasing amounts. Chloramphenicol's toxic side effects include bone marrow suppression, aplastic anemia, neurotoxicity, allergies, and gastrointestinal damage. Chloramphenicol is difficult to degrade naturally, and the threat posed by chloramphenicol wastewater is extremely serious.

[0003] Electrochemical reduction degradation of halogenated organic compounds involves the formation of active hydrogen (H*) via electrochemical cathode catalytic materials. This H* then reacts directly with the halogen atoms in the halogenated organic compounds, separating them from the compounds and ultimately degrading them. If the electrochemical cathode catalytic materials possess excellent reduction degradation properties, electrochemical reduction degradation technology could be an effective approach for treating wastewater containing halogenated organic compounds.

[0004] However, in the field of chloramphenicol wastewater treatment, the reduction and degradation performance of its electrochemical reduction and degradation catalytic materials is still poor, the repeated stable use performance is not ideal, and it cannot meet the requirements of large-scale industrial electrochemical reduction and degradation treatment of chloramphenicol wastewater. Summary of the Invention

[0005] In order to overcome the shortcomings of the existing technology, the present invention provides a method for preparing a foam copper-based catalytic material for electrochemical degradation of chloramphenicol wastewater. The foam copper-based catalytic material prepared by this method has high efficiency and excellent reduction degradation performance, and has excellent cyclic reuse stability, and can be suitable for the requirements of large-scale industrial electrochemical reduction degradation of chloramphenicol wastewater.

[0006] The technical solution adopted by the present invention to solve its technical problem is:

[0007] The present invention provides a method for preparing a foam copper-based catalytic material for electrochemically degrading chloramphenicol wastewater, comprising the following steps:

[0008] Step [1]: loading poly (3-thiopheneamide) on the surface of the copper foam substrate;

[0009] Step [2] synthesizing polyaminostyrene;

[0010] Step [3] converts the poly (3-thiopheneamide) on the surface of the foam copper substrate into a poly (3-thiopheneamide) / polyaminostyrene copper coordination polymer.

[0011] Preferably, the step [1] specifically includes the following operations:

[0012] a1. 3-trithiophenecarboxylic acid hydrazine and 3-thiopheneacetyl chloride were added to ethylene glycol dimethyl ether and mixed to form a base solution A; sodium bisulfite and urea were added to deionized water and mixed to form a catalytic regulator solution;

[0013] a2. A certain amount of catalytic regulating liquid was added to base liquid A and mixed to form a loading liquid. The foamed copper sample was immersed in the loading liquid and reacted at room temperature for 20-24 hours to obtain a foamed copper with poly (3-thiopheneamide) loaded on its surface, which was recorded as intermediate A.

[0014] Preferably, in step a1, the amount of 3-terthiophenecarboxylic acid hydrazine added to each liter of the base liquid A is 80-110 g, and the amount of 3-thiopheneacetyl chloride added is 40-80 g; the concentration of sodium bisulfite in the catalytic regulating liquid is 10-20 g / L, and the concentration of urea is 30-60 g / L.

[0015] Preferably, in step a2, the volume ratio of the catalytic regulating liquid to the base liquid A in the loading liquid is 1-2:5-9; and the weight of the foam copper immersed in each liter of the loading liquid is 130-170 g.

[0016] Preferably, the step [2] specifically includes the following operations:

[0017] b1. 2-aminostyrene and N,N-dimethylaniline were added to dimethyl sulfoxide and mixed to form an organic synthesis liquid; hexamethylenetetramine was added to deionized water and mixed to form an inorganic catalyst liquid;

[0018] b2. Add a certain amount of inorganic catalyst to the organic synthesis solution, react at room temperature for 22-26 hours, filter the solid product, and dry it under ventilation at room temperature for 10-12 hours to obtain polyaminostyrene.

[0019] Preferably, in step b1, the amount of 2-aminostyrene added to each liter of the organic synthesis liquid is 110-140 mL, and the amount of N,N-dimethylaniline added is 30-70 mL; and the concentration of hexamethylenetetramine in the inorganic catalyst liquid is 40-60 g / L.

[0020] Preferably, in step b2, the volume ratio between the inorganic catalyst liquid and the organic synthesis liquid is 5-7:2-4.

[0021] Preferably, the step [3] specifically includes the following operations:

[0022] c1. Methyl isobutylene copper, copper methanesulfonate and β-naphthalenesulfonic acid were added to deionized water and mixed to form a base solution B; 3-terthiophenecarboxylic acid hydrazine was added to ethylene glycol dimethyl ether and mixed to form an additive solution; a certain amount of the additive solution was added to the base solution B and mixed to form a conversion solution;

[0023] c2. Immersing the intermediate A in the conversion solution, while adding a certain amount of polyaminostyrene to the conversion solution, heating to 70-90°C, reacting for 8-12 hours, removing the foam copper sample, and drying it under ventilation at room temperature for 5-8 hours to obtain a foam copper loaded with a poly (3-thiopheneamide) / polyaminostyrene-copper coordination polymer, i.e., the foam copper-based catalytic material.

[0024] Preferably, in step c1, the amount of methyl isobutylene copper added to each liter of the base liquid B is 2-8 g, the amount of copper methanesulfonate added is 130-190 mL, and the amount of β-naphthalenesulfonic acid added is 20-50 g; the amount of 3-terthiophenecarboxylic acid hydrazine added to each liter of the additive liquid is 25-45 g; and the volume ratio between the additive liquid and the base liquid B in the conversion liquid is 2-3:7-9.

[0025] Preferably, in step c2, the weight of the intermediate A immersed in each liter of the conversion liquid is 100-130 g, and the amount of polyaminostyrene added to each liter of the conversion liquid is 80-140 g.

[0026] The positive effects of the present invention are as follows: the copper foam-based catalytic material prepared according to the method of the present invention has a poly(3-thiopheneamide) / poly(aminostyrene) copper coordination polymer loaded on the copper foam surface, wherein each copper ion accepts four lone pairs of electrons provided by the two oxygen atoms of the two carbonyl groups of poly(3-thiopheneamide) and the two amino nitrogen atoms of poly(aminostyrene) to form a coordination bond. Based on the above structural characteristics: the sulfur atom of the poly(3-thiopheneamide) forms a conjugated bond with the thiophene ring, forming an energy band structure with good conductive properties; the conductive properties of poly(aminostyrene) during the electrochemical reduction degradation process are relatively weak. Therefore, the coordination polymer can ensure a relatively fast reaction rate in the electrochemical reduction degradation of chloramphenicol while ensuring the relative stability of the poly(3-thiopheneamide) and poly(aminostyrene) composite coordination polymer; at the same time, the copper ions of the coordination polymer have unsaturated d orbitals, which can promote the formation of surface active hydrogen H*, thereby promoting the dechlorination and reduction degradation of chloramphenicol by the active hydrogen H*; in addition, the prepared copper foam-based catalytic material also has a relatively high hydrogen evolution overpotential, which can effectively inhibit the occurrence of hydrogen evolution side reactions during the electrochemical reduction degradation of chloramphenicol.

[0027] In summary, the foam copper-based catalytic material prepared according to the present invention has high-efficiency and excellent reduction degradation performance, and has excellent cyclic reuse stability, and can be applied to the requirements of large-scale industrial electrochemical reduction degradation of chloramphenicol wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a schematic diagram of the preparation process of the foam copper-based catalytic material of the present invention;

[0029] Figure 2 Schematic diagram of the microstructure of the foam copper-based catalytic material of the present invention;

[0030] Figure 3 The relative concentrations of residual chloramphenicol in the simulated chloramphenicol-containing wastewater treated with concentrations of 20 mg / L and 10 mg / L, respectively, in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention are shown;

[0031] Figure 4 1 is a graph showing the relationship between the number of uses and the relative concentration of residual chloramphenicol when Example 1, Comparative Example 1, and Comparative Example 2 are repeatedly used to treat simulated chloramphenicol-containing wastewater with a concentration of 20 mg / L;

[0032] Figure 5 This is a relationship diagram between the number of uses and the relative concentration of residual chloramphenicol when Example 1, Comparative Example 1, and Comparative Example 2 are repeatedly used to treat simulated chloramphenicol-containing wastewater with a concentration of 10 mg / L. DETAILED DESCRIPTION

[0033] Reference Figure 1 The present invention provides a method for preparing a foam copper-based catalytic material for electrochemically degrading chloramphenicol wastewater, comprising the following steps:

[0034] Step [1] is to load poly (3-thiopheneamide) on the surface of the copper foam substrate, specifically comprising the following operations:

[0035] a1. 3-trithiophenecarboxylic acid hydrazine and 3-thiopheneacetyl chloride are added to ethylene glycol dimethyl ether and mixed to form a base liquid A, wherein per liter of the base liquid A, 3-trithiophenecarboxylic acid hydrazine is added in an amount of 80 to 110 g and 3-thiopheneacetyl chloride is added in an amount of 40 to 80 g; sodium bisulfite and urea are added to deionized water and mixed to form a sodium bisulfite concentration of 10 to 20 g / L and a urea concentration of 30 to 60 g / L of a catalytic regulator;

[0036] a2. A certain amount of catalytic regulating liquid was added to base liquid A and mixed to form a loading liquid (the volume ratio of the catalytic regulating liquid to the base liquid A in the loading liquid was 1-2:5-9). The foam copper sample was immersed in the loading liquid (the weight of the foam copper immersed in each liter of the loading liquid was 130-170 g). The reaction was carried out at room temperature for 20-24 hours to obtain a foam copper with poly (3-thiopheneamide) loaded on the surface, which was recorded as intermediate A.

[0037] In this step, 3-terthiophenecarboxylic acid hydrazine and 3-thiopheneacetyl chloride are polymerized on the surface of the foam copper substrate to form poly (3-thiopheneamide). The structural formula of the poly (3-thiopheneamide) is:

[0038]

[0039] Step [2] synthesizing polyaminostyrene, specifically comprising the following operations:

[0040] b1. 2-aminostyrene and N,N- dimethylaniline are added to dimethyl sulfoxide and mixed to form an organic synthesis liquid, wherein per liter of the organic synthesis liquid, 2-aminostyrene is added in an amount of 110 to 140 mL and N,N- dimethylaniline is added in an amount of 30 to 70 mL; hexamine is added to deionized water and mixed to form an inorganic catalyst having a hexamine concentration of 40 to 60 g / L;

[0041] b2. The volume ratio of the inorganic catalyst liquid to the organic synthesis liquid is 5 to 7:2 to 4, and the inorganic catalyst liquid is added to the organic synthesis liquid, and the reaction is carried out at room temperature for 22-26 hours. The solid phase product is filtered and dried at room temperature for 10-12 hours to obtain polyaminostyrene.

[0042] In this step, polyaminostyrene is formed by polymerization of 2-aminostyrene, and the structural formula of the polyaminostyrene is:

[0043]

[0044] Step [3] converting the poly (3-thiopheneamide) on the surface of the copper foam substrate into a poly (3-thiopheneamide) / polyaminostyrene copper coordination polymer, specifically comprising the following operations:

[0045] c1. Methyl isobutylene copper, copper methanesulfonate and β-naphthalenesulfonic acid are added to deionized water and mixed to form a base solution B, wherein the amount of methyl isobutylene copper added per liter of the base solution B is 2 to 8 g, the amount of copper methanesulfonate added is 130 to 190 mL, and the amount of β-naphthalenesulfonic acid added is 20 to 50 g; 3-trithiophenecarboxylic acid hydrazine is added to ethylene glycol dimethyl ether and mixed to form an additive solution, wherein the amount of 3-trithiophenecarboxylic acid hydrazine added per liter of the additive solution is 25 to 45 g; the volume ratio between the additive solution and the base solution B is 2 to 3: 7 to 9. The additive solution is added to the base solution B and mixed to form a conversion solution;

[0046] c2. Immerse the intermediate A in the conversion solution (the weight of the intermediate A immersed in each liter of the conversion solution is 100-130 g), and simultaneously add a certain amount of polyaminostyrene to the conversion solution (the amount of polyaminostyrene added to each liter of the conversion solution is 80-140 g). Heat to 70-90° C., react for 8-12 hours, remove the copper foam sample, and dry it under ventilation at room temperature for 5-8 hours to obtain a copper foam with a surface loaded with a poly (3-thiopheneamide) / polyaminostyrene copper coordination polymer, i.e., the copper foam-based catalytic material. The microstructure diagram is shown in FIG. Figure 2 shown.

[0047] In this step, poly(3-thiopheneamide) and poly(aminostyrene) are used as ligands to form a poly(3-thiopheneamide) / poly(aminostyrene) copper coordination polymer with copper ions, and the reaction formula involved is:

[0048]

[0049] The preferred embodiments of the present invention are described below with examples.

[0050] Example 1

[0051] Preferred embodiment 1 of the present invention provides a method for preparing a foam copper-based catalytic material for electrochemical degradation of chloramphenicol wastewater, comprising the following steps:

[0052] Step [1] is to load poly (3-thiopheneamide) on the surface of the copper foam substrate, specifically comprising the following operations:

[0053] a1. 3-trithiophenecarboxylic acid hydrazine and 3-thiopheneacetyl chloride were added to ethylene glycol dimethyl ether and mixed to form a base solution A, wherein per liter of the base solution A, 3-trithiophenecarboxylic acid hydrazine was added in an amount of 90 g and 3-thiopheneacetyl chloride was added in an amount of 70 g; sodium bisulfite and urea were added to deionized water and mixed to form a sodium bisulfite concentration of 16 g / L, a urea concentration of 50 g / L of a catalytic regulator;

[0054] a2. A certain amount of catalytic regulating liquid was added to base liquid A to form a loading liquid (the volume ratio of catalytic regulating liquid to base liquid A in the loading liquid was 1:7). A copper foam sample was immersed in the loading liquid (the weight of the copper foam immersed in each liter of the loading liquid was 160 g). The reaction was carried out at room temperature for 23 hours to obtain a copper foam loaded with poly (3-thiopheneamide) on the surface, which was recorded as intermediate A.

[0055] Step [2] synthesizing polyaminostyrene, specifically comprising the following operations:

[0056] b1. 2-aminostyrene and N,N- dimethylaniline were added to dimethyl sulfoxide and mixed to form an organic synthesis liquid, wherein per liter of the organic synthesis liquid, 2-aminostyrene was added in an amount of 130 mL, N,N- dimethylaniline was added in an amount of 60 mL; hexamine was added to deionized water and mixed to form an inorganic catalyst having a hexamine concentration of 50 g / L;

[0057] b2. The volume ratio between the inorganic catalyst liquid and the organic synthesis liquid was 7:2 and the inorganic catalyst liquid was added to the organic synthesis liquid, and the reaction was carried out at room temperature for 25 hours. The solid phase product was filtered and dried at room temperature for 12 hours to obtain polyaminostyrene.

[0058] Step [3] converting the poly (3-thiopheneamide) on the surface of the copper foam substrate into a poly (3-thiopheneamide) / polyaminostyrene copper coordination polymer, specifically comprising the following operations:

[0059] c1. Methyl isobutylene copper, copper methanesulfonate and β-naphthalenesulfonic acid were added to deionized water and mixed to form a base solution B, wherein the amount of methyl isobutylene copper added per liter of the base solution B was 5 g, the amount of copper methanesulfonate added was 160 mL, and the amount of β-naphthalenesulfonic acid added was 40 g; 3-trithiophenecarboxylic acid hydrazine was added to ethylene glycol dimethyl ether and mixed to form an additive solution, wherein the amount of 3-trithiophenecarboxylic acid hydrazine added per liter of the additive solution was 40 g; the volume ratio between the additive solution and the base solution B was 3:8 and the additive solution was added to the base solution B, and mixed to form a conversion solution;

[0060] c2. The intermediate A was immersed in the conversion solution (the weight of the intermediate A immersed in each liter of the conversion solution was 120 g), and a certain amount of polyaminostyrene was added to the conversion solution (the amount of polyaminostyrene added to each liter of the conversion solution was 130 g). The solution was heated to 80°C and reacted for 10 hours. The foam copper sample was taken out and dried under ventilation at room temperature for 6 hours to obtain a foam copper with a surface loaded with a poly (3-thiopheneamide) / polyaminostyrene copper coordination polymer, i.e., the foam copper-based catalytic material, which is recorded as Example 1.

[0061] Comparative Example 1

[0062] This comparative example 1 provides a method for preparing a foam copper-based catalytic material for electrochemical degradation of chloramphenicol wastewater, comprising the following steps:

[0063] Step [1] is to load poly (3-thiopheneamide) on the surface of the copper foam substrate, specifically comprising the following operations:

[0064] a1. 3-trithiophenecarboxylic acid hydrazine and 3-thiopheneacetyl chloride were added to ethylene glycol dimethyl ether and mixed to form a base solution A, wherein per liter of the base solution A, 3-trithiophenecarboxylic acid hydrazine was added in an amount of 90 g and 3-thiopheneacetyl chloride was added in an amount of 50 g; sodium bisulfite and urea were added to deionized water and mixed to form a sodium bisulfite concentration of 15 g / L, a urea concentration of 40 g / L of a catalytic regulator;

[0065] a2. A certain amount of catalytic regulating liquid was added to base liquid A and mixed to form a loading liquid (the volume ratio of the catalytic regulating liquid to the base liquid A in the loading liquid was 1:6). The foam copper sample was immersed in the loading liquid (the weight of the foam copper immersed in each liter of the loading liquid was 140 g). The reaction was carried out at room temperature for 20-24 hours to obtain a surface-loaded copper foam with poly (3-thiopheneamide), which was recorded as Comparative Example 1.

[0066] Comparative Example 2

[0067] This comparative example 2 provides a method for preparing a foam copper-based catalytic material for electrochemically degrading chloramphenicol wastewater, comprising the following steps:

[0068] Step [1] is to load poly (3-thiopheneamide) on the surface of the copper foam substrate, specifically comprising the following operations:

[0069] a1. 3-trithiophenecarboxylic acid hydrazine and 3-thiopheneacetyl chloride were added to ethylene glycol dimethyl ether and mixed to form a base solution A, wherein per liter of the base solution A, 3-trithiophenecarboxylic acid hydrazine was added in an amount of 100 g and 3-thiopheneacetyl chloride was added in an amount of 70 g; sodium bisulfite and urea were added to deionized water and mixed to form a sodium bisulfite concentration of 15 g / L, a urea concentration of 50 g / L of a catalytic regulator;

[0070] a2. A certain amount of catalytic regulating liquid was added to base liquid A to form a loading liquid (the volume ratio of catalytic regulating liquid to base liquid A in the loading liquid was 2:7). A copper foam sample was immersed in the loading liquid (the weight of the copper foam immersed in each liter of the loading liquid was 150 g). The reaction was carried out at room temperature for 23 hours to obtain a copper foam loaded with poly (3-thiopheneamide) on the surface, which was recorded as intermediate A.

[0071] Step [2] synthesizing polyaminostyrene, specifically comprising the following operations:

[0072] b1. 2-aminostyrene and N,N- dimethylaniline were added to dimethyl sulfoxide and mixed to form an organic synthesis liquid, wherein per liter of the organic synthesis liquid, 2-aminostyrene was added in an amount of 130 mL, N,N- dimethylaniline was added in an amount of 40 mL; hexamine was added to deionized water and mixed to form an inorganic catalyst having a hexamine concentration of 50 g / L;

[0073] b2. The volume ratio of the inorganic catalyst liquid and the organic synthesis liquid was 5:3 and the inorganic catalyst liquid was added to the organic synthesis liquid, and the reaction was carried out at room temperature for 24 hours. The solid phase product was filtered and dried at room temperature for 11 hours to obtain polyaminostyrene.

[0074] Step [3] converts the poly(3-thiopheneamide) on the surface of the copper foam substrate into poly(3-thiopheneamide) / poly(aminostyrene), specifically comprising the following operations:

[0075] c1. β-naphthalenesulfonic acid was added to deionized water and mixed to form a base solution B, wherein the amount of β-naphthalenesulfonic acid added per liter of the base solution B was 30 g; 3-trithiophenecarboxylic acid hydrazine was added to ethylene glycol dimethyl ether and mixed to form an additive solution, wherein the amount of 3-trithiophenecarboxylic acid hydrazine added per liter of the additive solution was 30 g; the additive solution was added to the base solution B in a volume ratio of 3:8, and the conversion solution was formed by mixing;

[0076] c2. Immerse the intermediate A in the conversion solution (the weight of the intermediate A immersed in each liter of the conversion solution is 110 g), and at the same time add a certain amount of polyaminostyrene to the conversion solution (the amount of polyaminostyrene added in each liter of the conversion solution is 120 g), heat to 75°C, react for 10 hours, take out the foam copper sample, and dry it under ventilation at room temperature for 6 hours to obtain a foam copper loaded with poly 3-thiopheneamide / polyaminostyrene on the surface, which is recorded as Comparative Example 2; wherein the carbonyl group of poly 3-thiopheneamide in this step is The electron-withdrawing group, whose oxygen atom has a greater electronegativity than the carbon atom, has a strong electron-withdrawing ability, causing the electron pair to be biased toward the oxygen atom of the carbonyl group; the amine group of polyaminostyrene is an electron-donating group, and the electronegativity of the amine nitrogen is lower than that of carbon. Its electrons move toward the benzene ring of polyaminostyrene, which leads to a lower electron density of the amine group and makes the nitrogen of the amine group partially positively charged. Therefore, the partially positively charged nitrogen of the amine group of polyaminostyrene forms a chemical bond with the oxygen atom of the carbonyl group of poly-3-thiopheneamide, thereby reacting to form poly-3-thiopheneamide / polyaminostyrene. The reaction formula involved in this step is:

[0077]

[0078] In order to analyze the performance of electrochemical reduction degradation of chloramphenicol sewage in Example 1, Comparative Example 1 and Comparative Example 2, chloramphenicol was added to deionized water to form simulated chloramphenicol-containing sewage with a chloramphenicol addition of 20 mg / L and 10 mg / L, respectively. 100 ml of simulated chloramphenicol-containing sewage was poured into a beaker, and Example 1, Comparative Example 1 and Comparative Example 2 with a length, width and thickness of 4 cm × 2 cm × 1 cm were placed in a beaker. At the same time, in order to make the electrochemical reduction degradation process of the simulated chloramphenicol sewage have sufficient electrical conductivity, sodium sulfate was added to the simulated chloramphenicol sewage so that the sodium sulfate concentration in the simulated chloramphenicol sewage was 5 g / L. Comparative Example 1, Comparative Example 2 and Example 1 of the above-mentioned size were used as cathodes, stainless steel was used as anodes, and the reaction temperature was 4 mA / cm 2 The simulated chloramphenicol wastewater was degraded by constant current electrochemical reduction for 30 minutes, and the residual chloramphenicol concentration in the simulated chloramphenicol wastewater was measured by high performance liquid chromatography. The results are as follows Figure 3 As shown in the figure, it can be seen that the relative concentrations of residual chloramphenicol in the simulated chloramphenicol wastewater of 20 mg / L and 10 mg / L after electrochemical reduction degradation in Example 1 are only 0.02 and 0.01, respectively, which are significantly lower than the relative concentrations of residual chloramphenicol of 0.65 and 0.62 corresponding to Comparative Example 1, and also lower than the relative concentrations of residual chloramphenicol of 0.44 and 0.37 corresponding to Comparative Example 2.

[0079] Under the above-mentioned treatment conditions and treatment time, the simulated chloramphenicol wastewater of 20 mg / L and 10 mg / L was treated by cyclically repeating Example 1, Comparative Example 1 and Comparative Example 2. The relationship between the number of times of use and the relative concentration of residual chloramphenicol was as follows: Figure 4 and Figure 5 As shown in the figure, it can be seen that the residual chloramphenicol relative concentration of 100 ml of 20 mg / L and 10 mg / L simulated chloramphenicol sewage in Example 1 is only 0.08 and 0.06 when the electrochemical reduction degradation is repeated 15 times (one hour each time), which is significantly lower than the corresponding residual chloramphenicol relative concentration of 0.86 and 0.85 when the comparative example 1 is repeated 15 times, and also lower than the corresponding residual chloramphenicol relative concentration of 0.64 and 0.56 when the comparative example 2 is repeated 15 times. Obviously, Example 1 has stable and efficient recyclable characteristics.

[0080] In summary, the foam copper-based catalytic material prepared according to the present invention has high-efficiency and excellent reduction degradation performance, and has excellent cyclic reuse stability, and can be applied to the requirements of large-scale industrial electrochemical reduction degradation of chloramphenicol wastewater.

[0081] To illustrate in further detail, three additional examples are provided below.

[0082] Example 2

[0083] Preferred embodiment 2 of the present invention provides a method for preparing a foam copper-based catalytic material for electrochemical degradation of chloramphenicol wastewater, comprising the following steps:

[0084] Step [1] is to load poly (3-thiopheneamide) on the surface of the copper foam substrate, specifically comprising the following operations:

[0085] a1. 3-trithiophenecarboxylic acid hydrazine and 3-thiopheneacetyl chloride were added to ethylene glycol dimethyl ether and mixed to form a base liquid A, wherein per liter of the base liquid A, 3-trithiophenecarboxylic acid hydrazine was added in an amount of 80 g and 3-thiopheneacetyl chloride was added in an amount of 40 g; sodium bisulfite and urea were added to deionized water and mixed to form a sodium bisulfite concentration of 20 g / L, a urea concentration of 30 g / L of a catalytic regulator;

[0086] a2. A certain amount of catalytic regulating liquid was added to base liquid A to form a loading liquid (the volume ratio of catalytic regulating liquid to base liquid A in the loading liquid was 1:5). The foam copper sample was immersed in the loading liquid (the weight of the foam copper immersed in each liter of the loading liquid was 130 g). The reaction was carried out at room temperature for 20 hours to obtain a foam copper with poly (3-thiopheneamide) loaded on its surface, which was recorded as intermediate A.

[0087] Step [2] synthesizing polyaminostyrene, specifically comprising the following operations:

[0088] b1. 2-aminostyrene and N,N- dimethylaniline were added to dimethyl sulfoxide and mixed to form an organic synthesis liquid, wherein per liter of the organic synthesis liquid, 2-aminostyrene was added in an amount of 110 mL, N,N- dimethylaniline was added in an amount of 30 mL; hexamine was added to deionized water and mixed to form an inorganic catalyst having a hexamine concentration of 60 g / L;

[0089] b2. The volume ratio of the inorganic catalyst liquid to the organic synthesis liquid was 5:2, and the inorganic catalyst liquid was added to the organic synthesis liquid, and the reaction was carried out at room temperature for 22 hours. The solid phase product was filtered and dried under ventilation at room temperature for 10 hours to obtain polyaminostyrene.

[0090] Step [3] converting the poly (3-thiopheneamide) on the surface of the copper foam substrate into a poly (3-thiopheneamide) / polyaminostyrene copper coordination polymer, specifically comprising the following operations:

[0091] c1. Methyl isobutylene copper, copper methanesulfonate and β-naphthalenesulfonic acid were added to deionized water and mixed to form a base solution B, wherein the amount of methyl isobutylene copper added per liter of the base solution B was 2 g, the amount of copper methanesulfonate added was 130 mL, and the amount of β-naphthalenesulfonic acid added was 50 g; 3-trithiophenecarboxylic acid hydrazine was added to ethylene glycol dimethyl ether and mixed to form an additive solution, wherein the amount of 3-trithiophenecarboxylic acid hydrazine added per liter of the additive solution was 25 g; the volume ratio between the additive solution and the base solution B was 3:7. The additive solution was added to the base solution B and mixed to form a conversion solution;

[0092] c2. Immerse the intermediate A in the conversion solution (the weight of the intermediate A immersed in each liter of the conversion solution is 100 g), and at the same time add a certain amount of polyaminostyrene to the conversion solution (the amount of polyaminostyrene added to each liter of the conversion solution is 80 g), heat to 70°C, react for 12 hours, remove the foam copper sample, and dry it under ventilation at room temperature for 8 hours to obtain a foam copper with a surface loaded with a poly (3-thiopheneamide) / polyaminostyrene copper coordination polymer, i.e., the foam copper-based catalytic material.

[0093] Example 3

[0094] Preferred embodiment 3 of the present invention provides a method for preparing a foam copper-based catalytic material for electrochemical degradation of chloramphenicol wastewater, comprising the following steps:

[0095] Step [1] is to load poly (3-thiopheneamide) on the surface of the copper foam substrate, specifically comprising the following operations:

[0096] a1. 3-trithiophenecarboxylic acid hydrazine and 3-thiopheneacetyl chloride were added to ethylene glycol dimethyl ether and mixed to form a base liquid A, wherein per liter of the base liquid A, 3-trithiophenecarboxylic acid hydrazine was added in an amount of 110 g and 3-thiopheneacetyl chloride was added in an amount of 80 g; sodium bisulfite and urea were added to deionized water and mixed to form a sodium bisulfite concentration of 10 g / L, a urea concentration of 60 g / L of a catalytic regulator;

[0097] a2. A certain amount of catalytic regulating liquid was added to base liquid A to form a loading liquid (the volume ratio of catalytic regulating liquid to base liquid A in the loading liquid was 2:9). A copper foam sample was immersed in the loading liquid (the weight of the copper foam immersed in each liter of the loading liquid was 170 g). The reaction was carried out at room temperature for 24 hours to obtain a copper foam loaded with poly (3-thiopheneamide) on the surface, which was recorded as intermediate A.

[0098] Step [2] synthesizing polyaminostyrene, specifically comprising the following operations:

[0099] b1. 2-aminostyrene and N,N- dimethylaniline were added to dimethyl sulfoxide and mixed to form an organic synthesis liquid, wherein per liter of the organic synthesis liquid, 2-aminostyrene was added in an amount of 140 mL, N,N- dimethylaniline was added in an amount of 70 mL; hexamine was added to deionized water and mixed to form an inorganic catalyst having a hexamine concentration of 40 g / L;

[0100] b2. The volume ratio of the inorganic catalyst liquid to the organic synthesis liquid was 7:4, and the inorganic catalyst liquid was added to the organic synthesis liquid, and the reaction was carried out at room temperature for 26 hours. The solid phase product was filtered and dried at room temperature for 12 hours to obtain polyaminostyrene.

[0101] Step [3] converting the poly (3-thiopheneamide) on the surface of the copper foam substrate into a poly (3-thiopheneamide) / polyaminostyrene copper coordination polymer, specifically comprising the following operations:

[0102] c1. Methyl isobutylene copper, copper methanesulfonate and β-naphthalenesulfonic acid were added to deionized water and mixed to form a base solution B, wherein the amount of methyl isobutylene copper added per liter of the base solution B was 8 g, the amount of copper methanesulfonate added was 190 mL, and the amount of β-naphthalenesulfonic acid added was 20 g; 3-trithiophenecarboxylic acid hydrazine was added to ethylene glycol dimethyl ether and mixed to form an additive solution, wherein the amount of 3-trithiophenecarboxylic acid hydrazine added per liter of the additive solution was 45 g; the volume ratio between the additive solution and the base solution B was 2:9 and the additive solution was added to the base solution B, and mixed to form a conversion solution;

[0103] c2. Immerse the intermediate A in the conversion solution (the weight of the intermediate A immersed in each liter of the conversion solution is 130 g), and at the same time add a certain amount of polyaminostyrene to the conversion solution (the amount of polyaminostyrene added to each liter of the conversion solution is 140 g). Heat to 90°C, react for 8 hours, remove the foam copper sample, and dry it under ventilation at room temperature for 5 hours to obtain a foam copper with a surface loaded with a poly (3-thiopheneamide) / polyaminostyrene copper coordination polymer, i.e., the foam copper-based catalytic material.

[0104] Example 4

[0105] Preferred embodiment 4 of the present invention provides a method for preparing a foam copper-based catalytic material for electrochemical degradation of chloramphenicol wastewater, comprising the following steps:

[0106] Step [1] is to load poly (3-thiopheneamide) on the surface of the copper foam substrate, specifically comprising the following operations:

[0107] a1. 3-trithiophenecarboxylic acid hydrazine and 3-thiopheneacetyl chloride were added to ethylene glycol dimethyl ether and mixed to form a base liquid A, wherein per liter of the base liquid A, 3-trithiophenecarboxylic acid hydrazine was added in an amount of 95 g and 3-thiopheneacetyl chloride was added in an amount of 60 g; sodium bisulfite and urea were added to deionized water and mixed to form a sodium bisulfite concentration of 15 g / L, a urea concentration of 45 g / L of a catalytic regulator;

[0108] a2. A certain amount of catalytic regulating liquid was added to base liquid A to form a loading liquid (the volume ratio of catalytic regulating liquid to base liquid A in the loading liquid was 2:7). A copper foam sample was immersed in the loading liquid (the weight of the copper foam immersed in each liter of the loading liquid was 150 g). The reaction was carried out at room temperature for 22 hours to obtain a copper foam loaded with poly (3-thiopheneamide) on the surface, which was recorded as intermediate A.

[0109] Step [2] synthesizing polyaminostyrene, specifically comprising the following operations:

[0110] b1. 2-aminostyrene and N,N- dimethylaniline were added to dimethyl sulfoxide and mixed to form an organic synthesis liquid, wherein per liter of the organic synthesis liquid, 2-aminostyrene was added in an amount of 125 mL, N,N- dimethylaniline was added in an amount of 50 mL; hexamine was added to deionized water and mixed to form an inorganic catalyst having a hexamine concentration of 50 g / L;

[0111] b2. The volume ratio of the inorganic catalyst liquid and the organic synthesis liquid was 5:3 and the inorganic catalyst liquid was added to the organic synthesis liquid, and the reaction was carried out at room temperature for 24 hours. The solid phase product was filtered and dried at room temperature for 11 hours to obtain polyaminostyrene.

[0112] Step [3] converting the poly (3-thiopheneamide) on the surface of the copper foam substrate into a poly (3-thiopheneamide) / polyaminostyrene copper coordination polymer, specifically comprising the following operations:

[0113] c1. Methyl isobutylene copper, copper methanesulfonate and β-naphthalenesulfonic acid were added to deionized water and mixed to form a base solution B, wherein the amount of methyl isobutylene copper added per liter of the base solution B was 5 g, the amount of copper methanesulfonate added was 160 mL, and the amount of β-naphthalenesulfonic acid added was 35 g; 3-trithiophenecarboxylic acid hydrazine was added to ethylene glycol dimethyl ether and mixed to form an additive solution, wherein the amount of 3-trithiophenecarboxylic acid hydrazine added per liter of the additive solution was 35 g; the volume ratio between the additive solution and the base solution B was 3:8 and the additive solution was added to the base solution B, and mixed to form a conversion solution;

[0114] c2. The intermediate A is immersed in the conversion solution (the weight of the intermediate A immersed in each liter of the conversion solution is 115 g), and a certain amount of polyaminostyrene is added to the conversion solution (the amount of polyaminostyrene added to each liter of the conversion solution is 110 g). The solution is heated to 80°C and reacted for 10 hours. The foam copper sample is removed and dried under ventilation at room temperature for 6 hours to obtain a foam copper with a surface loaded with a poly (3-thiopheneamide) / polyaminostyrene-copper coordination polymer, i.e., the foam copper-based catalytic material.

[0115] The above are only preferred embodiments of the present invention. It should be understood that the description of the above embodiments is only used to help understand the method and core ideas of the present invention, and is not used to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, etc. made within the ideas and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a foam copper-based catalytic material for electrochemical degradation of chloramphenicol wastewater, characterized in that: The following steps are included: Step [1] Loading poly (3-thiopheneamide) on the surface of a copper foam substrate, specifically comprising: immersing the copper foam sample in a loading solution containing 3-terthiophenecarboxylic acid hydrazine and 3-thiopheneacetyl chloride to react, thereby obtaining a copper foam loaded with poly (3-thiopheneamide) on the surface, which is recorded as intermediate A; Step [2] Synthesis of polyaminostyrene; Step [3] converting the poly (3-thiopheneamide) on the surface of the copper foam substrate into a poly (3-thiopheneamide) / polyaminostyrene copper coordination polymer, specifically comprising the following operations: c1. Copper methyl isobutylene, copper methanesulfonate and β-naphthalenesulfonic acid were added to deionized water and mixed to form a base solution B; 3-trithiophenecarboxylic acid hydrazine was added to ethylene glycol dimethyl ether and mixed to form an additive solution; a certain amount of additive solution was added to the base solution B and mixed to form a conversion solution; c2. Immersing the intermediate A in the conversion solution, while adding a certain amount of polyaminostyrene to the conversion solution, heating to 70-90°C, reacting for 8-12 hours, removing the foam copper sample, and drying it under ventilation at room temperature for 5-8 hours to obtain a foam copper loaded with a poly (3-thiopheneamide) / polyaminostyrene-copper coordination polymer, i.e., the foam copper-based catalytic material.

2. The preparation method of a foam copper-based catalytic material for electrochemical degradation of chloramphenicol sewage according to claim 1, wherein The step [1] specifically includes the following operations: a1 3-trithiophenecarboxylic acid hydrazine and 3-thiopheneacetyl chloride were added to ethylene glycol dimethyl ether and mixed to form a base liquid A; sodium bisulfite and urea were added to deionized water and mixed to form a catalytic regulator liquid; a2. A certain amount of catalytic regulator solution was added to base solution A to form a loading solution. The copper foam sample was immersed in the loading solution and reacted at room temperature for 20-24 hours to obtain a copper foam loaded with poly (3-thiopheneamide) on the surface, which was recorded as intermediate A.

3. The preparation method of a foam copper-based catalytic material for electrochemical degradation of chloramphenicol sewage according to claim 2, wherein: In step a1, the amount of 3-terthiophenecarboxylic acid hydrazine added to each liter of the base liquid A is 80-110 g, and the amount of 3-thiopheneacetyl chloride added is 40-80 g; the concentration of sodium bisulfite in the catalytic regulating liquid is 10-20 g / L, and the concentration of urea is 30-60 g / L.

4. The preparation method of a foam copper-based catalytic material for electrochemical degradation of chloramphenicol sewage according to claim 2, wherein: In step a2, the volume ratio of the catalytic regulating liquid to the base liquid A in the loading liquid is 1-2:5-9; and the weight of the foam copper immersed in each liter of the loading liquid is 130-170 g.

5. The preparation method of a foam copper-based catalytic material for electrochemical degradation of chloramphenicol sewage according to claim 1, wherein The step [2] specifically includes the following operations: b1. 2-aminostyrene and N,N-dimethylaniline were added to dimethyl sulfoxide and mixed to form an organic synthesis liquid; hexamethylenetetramine was added to deionized water and mixed to form an inorganic catalyst liquid; b2. A certain amount of inorganic catalyst solution was added to the organic synthesis solution, and the reaction was carried out at room temperature for 22-26 hours. The solid phase product was filtered and dried under ventilation at room temperature for 10-12 hours to obtain polyaminostyrene.

6. A method for preparing a foam copper-based catalytic material for electrochemically degrading chloramphenicol sewage according to claim 5, characterized in that: In step b1, the amount of 2-aminostyrene added to each liter of the organic synthesis liquid is 110-140 mL, and the amount of N,N-dimethylaniline added is 30-70 mL; the concentration of hexamethylenetetramine in the inorganic catalyst liquid is 40-60 g / L.

7. The method for preparing a foam copper-based catalytic material for electrochemically degrading chloramphenicol sewage according to claim 5, wherein: In step b2, the volume ratio between the inorganic catalyst liquid and the organic synthesis liquid is 5-7:2-4.

8. The method for preparing a foam copper-based catalytic material for electrochemically degrading chloramphenicol sewage according to claim 1, wherein: In step c1, the amount of copper methyl isobutylene added to each liter of the base solution B is 2-8 g, the amount of copper methanesulfonate added is 130-190 mL, and the amount of β-naphthalenesulfonic acid added is 20-50 g; the amount of 3-terthiophenecarboxylic acid hydrazine added to each liter of the additive solution is 25-45 g; the volume ratio between the additive solution and the base solution B in the conversion solution is 2-3:7-9.

9. The method for preparing a foam copper-based catalytic material for electrochemically degrading chloramphenicol sewage according to claim 1, wherein: In step c2, the weight of the intermediate A immersed in each liter of the conversion liquid is 100-130 g, and the amount of polyaminostyrene added to each liter of the conversion liquid is 80-140 g.

Citation Information

Patent Citations

  • Copper complex having electrocatalytic activity on hydrogen peroxide and preparation method thereof

    CN103467498A

  • Pd / foamy copper electrode and preparation method and application thereof

    CN107557770A